Pasig-Laguna linkage a mixed-use transport terminal riverfront development - Mediarito, Angelica Mae F. (College of Architecture, University of the Philippines Diliman, 2022)
Connecting cities is not just utilizing transportation to move from one place to another, but rather how an individual is able to actively connect and participate in their society. We see a ripple effect of how many economic and ecological disadvantages occur due to the lack of proper urban planning. As such, the project focuses on how megaregions emerge as a result of urban growth and interactions. It also addresses issues of mobility, class division, environmental degradation, and other consequences of poor regional connectivity and how it imposes threats to our cities, the economy, public health, and the environment. The project then aims to propose a tri-city plan that would connect Metro Manila to other provinces in Southern Luzon through the use of waterway transportation. Introducing a new mode of transportation system would not only promote accessibility but also give a huge opportunity to maximize and rehabilitate our natural waterway resources at the same time. Most notably, the site is located on the outskirts of Taguig City, between Pasig River and Laguna de Bay, both of which are considered fragile bodies of water. The tri-city project would be incorporated into the country's current and future government projects since its vision is not to replace these developments but to enhance connectivity and intermodality. By closely examining the relationships between cities, waterways, and people and how they benefit from each other, the project sheds new light on how connecting cities and contribute to inclusive growth within the country.